Implementation of Differentiated Learning in The Independent Curriculum in The History Subject in Grade X-A of SMA Negeri 4 Palu - Muliani; Rore, Idrus; Hasan; Prasetyawati, Priyatna (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Implementation of Differentiated Learning of the Independent Curriculum in History Subjects in Class X-A of SMA Negeri 4 Palu. Thesis. History Education Study Program, Department of Social Science Education, Faculty of Teacher Training and Education, Tadulako University. Supervisor Idrus A Rore. This study aims to analyze the implementation of differentiated learning in the Independent Curriculum in History subjects in class X-A of SMA Negeri 4 Palu. This study uses a qualitative descriptive research method. Data collection techniques used in this study are observation, interviews, and documentation. Based on the results of this study, the implementation of differentiated learning in the independent curriculum in history subjects in class X shows that the understanding of history teachers at SMA Negeri 4 Palu regarding the concept of differentiated learning in the Independent Curriculum is quite good but still needs to be improved. Teachers understand that differentiation aims to adapt learning to the needs, interests, and readiness of students, and implement it through varied assignments, student grouping, and the use of different media. However, the implementation still faces obstacles such as limited time, facilities, and a large number of students, as well as some teachers who do not fully understand this concept. Nevertheless, support in the form of training and teacher discussions has helped increase student motivation and engagement in history learning.